Teaching Quality Management at the Course Level - Pavlina, Krešimir; Banek Zorica, Mihaela; Pongrac Pavlina, Ana (2009)
This paper presents quality assurance systems used in the countries of the world and presents processes for internal and external quality assurance in institutions of higher education. By analysis of existing systems for control of the quality of teaching, it has been found that all observed the quality of teaching only to the course level. The central part of this paper presents developed model for quality management at the course level that is based on continuous assessment during semester. Evaluation is conducted at the level of individual teaching topic using on-line questionnaire. The model presents a way of statistical analysis of the results obtained by evaluation of teaching quality. This has enabled improvement in teaching practices within each individual teaching topic, as well as the improvement of the entire course. Based on the model presented in this paper, researchers created on-line quality management system.
Projekt MZOS
ENG